CAFFEINE AND PHYSICAL PERFORMANCE: A LITERATURE REVIEW ON BIOCHEMICAL MECHANISMS AND IMPLICATIONS FOR MUSCLE MASS AND STAMINA - Luluk Hermawati; Hilizza Awalina; Nur Bebi Ulfah Irawati; Amanah Eva Fidusia; Erika Agustianti; Fathurrohim Fathurrohim (Journal of Sport Science and Tourism Activity, 2026)
Caffeine is the most widely consumed stimulant compound globally and is well known for its ability to enhance alertness and reduce the perception of fatigue. In the context of sports and physical activity, caffeine has been identified as an effective ergogenic aid, improving both endurance and cognitive performance during intense exercise. This literature review aims to systematically evaluate the primary biochemical mechanisms of caffeine relevant to physical performance enhancement, particularly through its effects on the central nervous system and muscle metabolism. Biochemically, caffeine primarily functions by blocking adenosine receptors, thereby influencing neurotransmission and increasing sympathetic activity. Additionally, caffeine has been shown to affect energy substrate mobilization by enhancing lipolysis and sparing muscle glycogen. Interestingly, recent evidence suggests that caffeine also plays a role in muscle mass regulation through the activation of molecular pathways such as AMPK and mTOR. AMPK activation enhances metabolic efficiency and energy utilization, while mTOR is involved in protein synthesis and muscle hypertrophy, positioning caffeine as a potential candidate to support training adaptation and muscle mass maintenance. However, caffeine’s effectiveness is not uniform across individuals and may be influenced by various factors such as dosage, timing of consumption, type of exercise, as well as genetic and habitual factors. Therefore, a comprehensive understanding of caffeine’s mechanisms of action is crucial for maximizing its benefits in supporting physical performance safely and effectively. This article summarizes the latest scientific findings providing physiological and molecular foundations regarding caffeine’s role in enhancing endurance and muscle mass, and offers insights for its application in sports and health practices.